Rad6 Regulates Conidiation by Affecting the Biotin Metabolism in Beauveria bassiana - Yuhan Guo; Haomin He; Yi Guan; Longbin Zhang (Journal of Fungi)
Rad6 is a canonical ubiquitin-conjugating enzyme known for its role in regulating chromosome-related cellular processes in yeast and has been proven to have multiple functions in Beauveria bassiana, including insect-pathogenic lifestyle, UV damage repair, and conidiation. However, previous studies have only reported the key role of Rad6 in regulating conidial production in a nutrient-rich medium, without any deep mechanism analyses. In this study, we found that the disruption of Rad6 leads to a profound reduction in conidial production, irrespective of whether the fungus is cultivated in nutrient-rich or nutrient-poor environments. The absence of rad6 exerts a suppressive effect on the transcription of essential genes in the central developmental pathway, namely, brlA, abaA, and wetA, resulting in a direct downregulation of conidiation capacity. Additionally, mutant strains exhibited a more pronounced decline in both conidial generation and hyphal development when cultured in nutrient-rich conditions. This observation correlates with the downregulation of the central developmental pathway (CDP) downstream gene vosA and the upregulation of flaA in nutrient-rich cultures. Moreover, single-transcriptomics analyses indicated that irregularities in biotin metabolism, DNA repair, and tryptophan metabolism are the underlying factors contributing to the reduced conidial production. Comprehensive dual transcriptomics analyses pinpointed abnormal biotin metabolism as the primary cause of conidial production decline. Subsequently, we successfully restored conidial production in the Rad6 mutant strain through the supplementation of biotin, further confirming the transcriptomic evidence. Altogether, our findings underscore the pivotal role of Rad6 in influencing biotin metabolism, subsequently impacting the expression of CDP genes and ultimately shaping the asexual life cycle of B. bassiana.